SPIRITUAL DIMENSION OF FERTILITY CULT AND POWER IN WOMAN - Pandharipande, Rajeshwari (Journal of Dharma, 1988)
Various perspectives on the role of woman in the Indian society have been presented in a number of studies (e.g., Altekar 1938, 1962, Bhattacharya 1977, Brown 1974, Gatwood 1985, Kosambi 1965, Shrivastava 1979, Tyler 1973, and Wadley 1977). These studies analyzed the issues related to woman within the framework of anthropology, sociology, and philosophy. Most studies describe or explain the role of woman either within the ideological framework (religious ideology/ beliefs, etc.). or within the socioeconomic structure of the society. However, those studies do not generally explain the exact link between the ideological framework and the role of woman in the society. Gatwood (1985 :9), while discussing the impact of the ideological framework on the society, claims, 'The presence or absence of a new belief, idea, or value can make or break a proposed sociocultural material change," One method of examining the relationship between the ideology and the social structure is to trace the parallel developments in the ideology and the social structure through the history, For example, in order to claim that there existed a correlation between the structure of religious beliefs and the role of/image of woman in the early Indian civilizations, it is important to trace the parallel developments in both the ideological framework and the role/image of woman in society at various points in the history, The co-existence of the two parallel system does not necessarily specify the direction of influence, but it certainly establishes the link between the two. The major thesis of this paper is that there exists a link between the interpretation of the "feminine principle" within the religious system and the role of woman in the corresponding society.